Open access to science: 2009 report, and 2010 prospects - Abadal, Ernest; García-Abad, Francisca; Melero, Remedios; Rodríguez-Gairín, Josep-Manuel (Anuario ThinkEPI, 2010)
The major events in Spain during 2009 in the field of Open access to science are described and contextualized with the international environment. We offer 2009 statistical data and discuss the main achievements in three broad areas: repositories, journals and policies. The report ends with the 2010 prospects for each of the areas.
Keywords: Open access; Repositories; Scientific journals; Open access policies; Prospects.